1987
DOI: 10.1007/bf00177925
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption in free-feeding rats: procedural, genetic and pharmacokinetic factors

Abstract: Voluntary consumption of alcohol by rats (i.e. in the absence of food or water deprivation, sweetening of the alcohol solution, etc.) that results in the attainment of behaviorally significant or pharmacologically detectable blood alcohol levels (BALs) has been difficult to demonstrate. In this study, we showed that free-feeding Wistar rats given access to increasingly concentrated solutions of alcohol in separate "drinking" cages on a 1-h per day basis drank on average close to 1 g/kg, resulting in average BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(43 citation statements)
references
References 22 publications
(21 reference statements)
3
40
0
Order By: Relevance
“…Adding sweeteners to ethanol solutions to produce higher ethanol intake is not a new experimental strategy. Some of the disadvantages of earlier procedures are, however, circumvented in the present model, such as the need for food deprivation (e.g., Macdonall and Marcucella, 1979) or water deprivation (e.g., Hubbell et al, 1986;Reid et al, 1996;Gardell et al, 1997), or the lack of a defined BAL criterion (e.g., Stewart and Grupp, 1984;Gill et al, 1986;Linseman, 1987;Sinclair et al, 1992). Although genetic manipulations have been used to produce animals that reliably and voluntarily consume large quantities of ethanol (e.g., HARF animals, Lê et al, 2001;P rats, Murphy et al, 1986), selective breeding is not a practical solution for most laboratories.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Adding sweeteners to ethanol solutions to produce higher ethanol intake is not a new experimental strategy. Some of the disadvantages of earlier procedures are, however, circumvented in the present model, such as the need for food deprivation (e.g., Macdonall and Marcucella, 1979) or water deprivation (e.g., Hubbell et al, 1986;Reid et al, 1996;Gardell et al, 1997), or the lack of a defined BAL criterion (e.g., Stewart and Grupp, 1984;Gill et al, 1986;Linseman, 1987;Sinclair et al, 1992). Although genetic manipulations have been used to produce animals that reliably and voluntarily consume large quantities of ethanol (e.g., HARF animals, Lê et al, 2001;P rats, Murphy et al, 1986), selective breeding is not a practical solution for most laboratories.…”
Section: Discussionmentioning
confidence: 95%
“…Collectively, these models have weak construct validity for the human condition (i.e., humans do not consume ethanol because they are hungry or thirsty). Other studies have produced voluntary ethanol consumption by rats during limited access sessions without the use of any of these manipulations but those studies either did not produce BALs (0.08 g%) determined by NIAAA to be the defining factor in binge alcohol drinking (e.g., Stewart and Grupp, 1984;Gill et al, 1986;Linseman, 1987) or did not measure BALs (e.g., Macdonall and Marcucella, 1979). Finally, genetic manipulations have been used to produce rats selectively bred for high alcohol preference based on either continuous access ethanol intakes (e.g., alcohol-preferring P rats; Murphy et al, 1986) or limited access ethanol intakes (i.e., high alcohol-consuming HARF rats; Lê et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…While the intake of alcohol was variable across the experiments, the amounts of the drug consumed exceed levels of intake that have been shown to produce reliable pharmacological effects (cf. Linseman 1987;Weiss et al 1990). In STUDY 1, it was found that during the maintenance phase, low doses of naltrexone and fluoxetine decrease lever presses for alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature was maintained at 21 Ϯ 1 Њ C and lights were on from 7 a.m. to 7 p.m. Rats were initially trained to consume alcohol in a limited access procedure (Linseman 1987). Briefly, rats were provided with access to an alcohol solution and water in modified "Richter" tubes for 30 min/day in drinking cages.…”
mentioning
confidence: 99%
“…The temperature was maintained at 21±1°C and the lights were on from 7 a.m. to 7 p.m. Rats were initially trained to consume alcohol in a limited-access procedure (Linseman 1987). The rats were given access to an alcohol solution and water in modified Richter tubes for 30 min/day in drinking cages.…”
Section: Subjectsmentioning
confidence: 99%